Menyoal hak maternitas pengemudi ojek daring di Bekasi Timur: Disregarding Maternity Entitlement for Online Motorcycle Taxi Drivers in East Bekasi - Abigail, Sifra Prilideo; Damanik, Janianton (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2025)
Workers, including women with maternity needs, possess legally protected rights. However, online motorcycle taxi drivers in Indonesia face different circumstances due to the partnership model promoted by online transport service companies, classifying them as partners and thus preventing unionization. Nonetheless, ASPEK Indonesia considers online motorcycle taxi drivers as workers who need to unionize. By posing the question of how trade unions strive to protect the maternity rights of online motorcycle taxi drivers, this study aims to investigate the efforts made by Serikat Pekerja Platform Daring to safeguard these rights. The research adopts a qualitative approach with a case study strategy. Data were collected through interviews, observations, and documentation, and analyzed through data reduction, data display, and conclusion drawing/verification. The findings indicate that maternity rights for online motorcycle taxi drivers have not been pursued by trade unions or the female drivers themselves. According to social reproduction theory, this disregardment will negatively impact the future workforce's health and education. Therefore, the maternity rights of informal workers, such as women driving for digital transportation platforms, need to be responsibly addressed.